THE INFLUENCE OF CUSTOMER RELIGIOSITY COMMITMENT ON CONTINUANCE INTENTION OF SHARIA MOBILE BANKING WITH TRUST IN MOBILE BANKING AS A MEDIATOR AMONG MILLENNIAL GENERATION IN KLATEN REGENCY - Abdul Hadi Hari; Rizky Windar Amelia; Abdul Haris (Jurnal Ilmiah Ekonomi Islam, 2025)
Abstract This study aims to analyze the influence of Consumer Religiosity Commitment on Sharia Mobile Banking Continuance Intention with Trust in Sharia Mobile Banking as a mediating variable. A quantitative approach was employed, with data collected through questionnaires from users of Sharia mobile banking services. The results of the analysis reveal that Consumer Religiosity Commitment has a positive and significant effect on Sharia Mobile Banking Continuance Intention (coefficient 0.672; t = 12.758; p < 0.001) and on Trust in Sharia Mobile Banking (coefficient 0.657; t = 11.891; p < 0.001). Furthermore, Trust in Sharia Mobile Banking also has a significant positive effect on Sharia Mobile Banking Continuance Intention (coefficient 0.695; t = 12.879; p < 0.001) and mediates the relationship between Consumer Religiosity Commitment and Sharia Mobile Banking Continuance Intention (mediation coefficient 0.456; t = 8.383; p < 0.001). The findings indicate that trust plays a pivotal role as a mediator in linking religiosity commitment with the intention to continue using Sharia mobile banking. Consumer trust in secure, reliable services aligned with Sharia principles strengthens the impact of religiosity on consumer loyalty. Managerial implications of this study highlight the importance for Islamic banks to enhance trust through features such as security, service transparency, and adherence to Sharia values. Additionally, marketing strategies emphasizing the alignment of services with religiosity values can foster loyalty and the sustained use of Sharia mobile banking services.